Analysis of Market Services Compared to Public Services in Romania - Marian Ionel (Ovidius University Annals: Economic Sciences Series, 2021)
Market services are services specific to a market economy that aim at both meeting the needs of consumers of services and making a profit for providers of such services. These services can be market services provided to the population that seek to meet the needs of the population as consumers of services, as well as market services for businesses that are part of the business sector generating profit for entrepreneurs. But a society also needs public services, especially services financed from the state budget. In Romania, at present, these services have an important role. Although they have seen an upward trend, both market services and public services have been severely affected by the crisis caused by the COVID pandemic 19.